MENGEMBANGKAN PROFESIONALISME PENDIDIK GURU (Kajian Konseptual Dan Operasional) - I G. A. K. Wardani (LPPM Universitas Terbuka, 2012)
The role of teacher educators is becoming more and more important in fulfilling the need of profesional teachers as stated in the Indonesian Republic Law #14/2005 on Teacher and Lecturer. In order to be able to educate profesional teachers and teacher candidates, the teacher educators alone should be profesional, and have willingness to continuously develop profesionalism. Developing profesionalism is a must for teacher educators, due to four reasons: (1) the nature of profesionalism, (2) the rapid development of science, technology and arts, (3) the life-long learning paradigm, and (4) the demand of Law # 14/2005 on Teacher and Lecturer. But the data on teacher educators from several Teacher Education Institutions indicate that not all of teacher educators show willingness to develop profesionalism. Therefore, profesionalism development should be encouraged by all parties related to teachers and teacher educators. There are many activities that can be undergone by teacher educators in order to develop profesionalism, some of which are: taking further study, taking relevant courses, regular self reflection, joining academic activities (seminar, workshop, training,etc.), school familiarization, conducting research, and publishing scientific article. Peran pendidik guru menjadi lebih dan lebih penting dalam memenuhi kebutuhan guru profesional sebagaimana tercantum dalam Undang-Undang Republik Indonesia # 14/2005 tentang Guru dan Dosen. Agar dapat mendidik guru profesional dan calon guru, pendidik guru sendiri harus profesional, dan memiliki kemauan untuk terus mengembangkan profesionalisme. Mengembangkan profesionalisme adalah suatu keharusan bagi pendidik guru, karena empat alasan: (1) sifat profesionalisme, (2) perkembangan pesat ilmu pengetahuan, teknologi dan seni, (3) paradigma pembelajaran seumur hidup, dan (4) permintaan Hukum # 14/2005 tentang Guru dan Dosen. Namun data pada pendidik guru dari Lembaga Pendidikan Guru beberapa menunjukkan bahwa tidak semua pendidik guru menunjukkan kesediaan untuk mengembangkan profesionalisme. Oleh karena itu, pengembangan profesionalisme harus didorong oleh semua pihak yang terkait dengan guru dan pendidik guru. Ada banyak kegiatan yang dapat dialami oleh pendidik guru dalam rangka mengembangkan profesionalisme, beberapa diantaranya adalah: mengambil studi lebih lanjut, mengambil kursus yang relevan, refleksi diri secara teratur, bergabung dengan kegiatan akademik (seminar, lokakarya, pelatihan, dll), pengenalan sekolah , melakukan penelitian, dan penerbitan artikel ilmiah.